2013
DOI: 10.1080/21635781.2013.830062
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization Among Women Veterans: Health, Health Care Service Use, and Opportunities for Intervention

Abstract: Intimate partner violence (IPV) victimization is a major source of morbidity and mortality for women. We know little about the IPV experiences among the growing population of women military veterans in the United States. To address this gap in knowledge, we conducted a retrospective review of medical records of 533 women veteran patients age 55 and younger at a Veterans Affairs (VA) medical center to identify the scope of IPV exposure and associated demographic, health, and health care service use characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
(20 reference statements)
5
21
1
Order By: Relevance
“…[42][43][44][45] Thus, women may have prematurely separated from military service due to violence and then also be at risk for future violence. This study replicated findings from smaller samples of women Veteran VHA patients 22,34 indicating that women who experienced MST were more than twice as likely to report past-year IPV relative to women who did not have a MST history. As such, MST prevention and response programs may be particularly fruitful points of intervention for more generalized violence prevention.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[42][43][44][45] Thus, women may have prematurely separated from military service due to violence and then also be at risk for future violence. This study replicated findings from smaller samples of women Veteran VHA patients 22,34 indicating that women who experienced MST were more than twice as likely to report past-year IPV relative to women who did not have a MST history. As such, MST prevention and response programs may be particularly fruitful points of intervention for more generalized violence prevention.…”
Section: Discussionsupporting
confidence: 79%
“…Race and ethnicity were not associated with past-year IPV, as other Veteran studies have found. 22,34 Studies of screening implementation should attend to race, however, as non-white race was associated with nonresponse to IPV items. Past-year IPV was associated with indicators of economic hardship, including lower levels of employment, receipt of public assistance, low income and past-year homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…We identified documentation of IPV through a review of all provider progress notes, for all visit types, during the study period. Further details about the sample selection and identification of IPV are documented elsewhere (Dichter & Marcus, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of women veterans receiving care at a VA Medical Center, those with documented IPV experience had higher rates of mood disorders, alcohol/drug dependence, sleep problems, and PTSD, as well as other health conditions compared to women without documented IPV exposure. They also had more frequent health care encounters and were more likely to use emergency department and mental or behavioral health care services (Dichter & Marcus, 2013). IPV victimization may compound health problems for women veterans and add existing burden to the VA health care system.…”
Section: Women Veterans and Ipvmentioning
confidence: 95%